Description of a proposed simple semi-objective histological scale for the assessment of dermal melanophages in inflammatory skin diseases - Rajiv Sharad Joshi (Wolters Kluwer Medknow Publications, 2018)
Background: Dermal melanophages are a common histopathological finding in several inflammatory skin diseases and may be seen even in clinically normal-looking skin. Clinically hyperpigmented and hypopigmented conditions as well as nonpigmented lesions show melanophages which cannot always be correlated with the clinical appearance of the lesion biopsied. No literature exists to help assess the significance of dermal melanophages in inflammatory diseases and correlate their presence with the pathophysiology of the disease biopsied. Methodology: This is a retrospective study of 100 skin biopsies in patients with brown skin, which had mentioned dermal melanophages in the histopathological report. A simple-to-use semi-objective scale (score of 3-10) was used to assess the score of the dermal melanophages. This was done by a dermatopathologist who was blinded to the clinical and histopathological diagnoses. A correlation of the dermal melanophage score was attempted with the clinical/histological diagnoses and known pathogenesis of the diseases. Results: A variety of skin diseases were included in this study which could be broadly grouped into hypopigmented (10 cases, average scores 4), nonpigmented interface diseases (20 cases, average score 6.66), miscellaneous nonpigmented dermatosis (17 cases, average scores 5.3), and hyperpigmented (53). The hyperpigmented group was subdivided into those that were known to show predominantly epidermal melanin (13 cases, average score 4.58) and those who have predominantly dermal melanin following interface dermatitis (29 cases, average score 8.67) and dermal melanosis without interface dermatitis (11 cases, average score 6.18). Conclusions: This scale can be used to determine the significance of dermal melanophages in inflammatory skin diseases. Scores >6 suggest hyperpigmentary conditions due to the presence of dermal melanophages. Low scores of 3-5 are not significant and are seen in epidermal hypermelanoses, hypopigmented conditions, and other varied nonpigmented dermatoses.